Terrorism, Asymmetric Warfare, and Weapons of Mass Destruction : Defending the U.S. Homeland - Cordesman, Anthony H. (London Pentagon Press, 2008)
New threats require new thinking. State attacks involving long-range missiles or conventional military forces are not the only threat to the U.S. homeland. Covert attacks by state actors, state use of proxies, independent terrorist and extremist attacks by foreign groups or individuals--and even by residents of the United States--are significant issues for future U.S. security. In this comprehensive work, Cordesman offers a range of recommendations, from reevaluating what constitutes a threat and bolstering homeland defense measures, to improving resource allocation and sharpening intelligence. Annotation. Cordesman (Middle East program, Center for Strategic and International Studies) argues that homeland defense must respond to a constantly changing threat, and especially to the kind that may be impossible to predict, and which may emerge as a pattern of attack in the years to come.
Keywords: United States -- Defenses. -- United States -- Military Policy -- Terrorism -- United States -- Prevention -- Military Policy -- Weapons of Mass Destruction